Pengaruh Kompetensi, Prestasi Kerja, dan Pengalaman Kerja terhadap Pengembangan Karier Pegawai Kantor Wilayah Kementerian Agama Provinsi Sulawesi Selatan - Khaer, Nisaul; Hidayati, Ulfa (Institut Agama Islam Negeri Parepare, 2023)
This research aims to examine the impact of competence, work performance, and work experience on the career development of employees in the Regional Office of the Ministry of Religious Affairs in South Sulawesi Province. The sample for this study comprised 142 respondents who were civil servants employed at the Regional Office. To address the research objective, the author employed the multiple linear regression analysis technique with the aid of SPSS software. The findings of this study provide empirical evidence of the positive and significant influence of competence, work performance, and work experience on the career development of employees in the Regional Office of the Ministry of Religious Affairs in South Sulawesi Province. These results underscore the importance of enhancing competence, improving work performance, and acquiring relevant work experience as pivotal factors in advancing the careers of employees within this organizational context. The implications of this research highlight the need for organizations to prioritize competence development programs, performance management systems, and opportunities for employees to gain diverse work experiences. By investing in these areas, organizations can foster the professional growth and career advancement of their employees in the Regional Office of the Ministry of Religious Affairs in South Sulawesi Province. Future research can further explore additional variables or contexts to gain a comprehensive understanding of career development within the ministry and provide valuable insights for effective human resource management practices.